Memory function performance in individuals classified as overweight, obese, and normal weight - Berbegal, Marina; Tomé, Mario; Sánchez-SanSegundo, Miriam; Zaragoza-Martí, Ana; Hurtado-Sánchez, José Antonio (Frontiers in Nutrition, 2022)
Evidence accumulated to date about the relationship between cognitive impairments and adults with overweight and obesity suggest that excess weight has a great impact on memory function. Nevertheless, most literature has focused only on studying the influence of working memory and episodic memory. This study aimed to examine the potential associations of clinical and anthropometric measures (BMI, WHR, body fat, visceral fat, muscle mass, hypertension) with six memory domains including contextual memory, short-term visual memory, short-term memory, non-verbal memory, short-term phonological memory and working memory in a sample of 124 individuals with overweight (n = 33), obesity (n = 53) and normal weight (n = 38). The results obtained show that, after controlling for employment situations, obese people had poorer short-term phonological memory and working memory than those with normal weight. Bivariate correlations show that measures of weight, BMI, Waist–Hip Ratio index, and visceral fat were inversely associated with memory function. However, neither body fat nor muscle mass were significant predictors of memory function. Higher systolic blood pressure was also associated with worse memory function. The study provides evidence of the importance of adiposity in health and memory function. Future research should advance in this comprehension, analyzing the possible mechanisms of the influence of clinical and anthropometric measures in the different types of memory.